Prevalence of aflatoxin, ochratoxin and deoxynivalenol in cereal grains in northern Uganda: Implication for food safety and health - Echodu, Richard; Malinga, Geoffrey Maxwell; Moriku Kaducu, Joyce; Ovuga, Emilio; Haesaert, Geert (Toxicology reports, 2019)
Mycotoxin contamination of cereals is a significant health risk for humans and animals, particularly in developing countries. To gain insight into food safety related to agricultural practices, we assessed levels of mycotoxin contamination in 105 samples of food grains raised and stored for consumption by rural households in the postconflict districts of Kitgum and Lamwo in Northern Uganda. Aflatoxin, ochratoxin and deoxynivalenol (DON) contamination was assessed by quantitative enzyme-linked immunosorbent assay. Total aflatoxin in the foods analyzed varied from nd (not detected) to 68.2 μg/Kg. Ochratoxin ranged from 0.1 to 16.4 μg/Kg. DON ranged from nd to 2606 μg/Kg. The mean concentration of total aflatoxins was significantly higher (P=0.002) in sorghum than in millet, maize and sesame seeds. Frequency of co-occurrence of two mycotoxins ranged from 8.3 to 100%, with the highest being aflatoxin and ochratoxin in sorghum. Co-occurrence of all three mycotoxins ranged from 8.3 to 35.3%, with the highest again being in sorghum. Mean levels of aflatoxins concentration in sorghum samples were 11.8 μg/Kg, exceeding the Ugandan national regulatory limits of 10 μg/Kg. Furthermore, 46.5% of the sorghum consumed in both districts exceeded this limit, and 86.1% of sorghum samples exceeded the European Union (E.U.) maximum tolerable limit of 4 μg/Kg. The Estimated Daily Intake (EDI) and Hazard Indices (HI) values were in the range of 1.2×10−5–91.521 and 1.3×10−7 to 0.0059, respectively. In conclusion, our results provide evidence of high levels of mycotoxin contamination and co-occurrence in food grains in Northern Uganda with aflatoxins and ochratoxins at high levels in all the cereal types analyzed. Consumption of cereals cultivated in this region poses no health risk of mycotoxins exposure since HI values obtained were less than 1.
Keywords: Aflatoxin; Ochratoxin; Deoxynivalenol; Food grains; Food safety; Uganda